The Contrastive Analysis of Kinship Terminology in Cina Benteng and Hakka (Khek) - Inggrit Laurenza; Sonya Ayu Kumala (SUAR BETANG, 2022)
Kinship terminology is a way of addressing someone who is bound to themselves because of blood, descent, and marriage. Kinship terminology is culturally bounded. Kinship systems are widely discussed in different areas of humanity studies, such as linguistics studies. Terminologies in the kinship system of both Cina Benteng and Khek will be used as the linguistic evidence of this research. Since it is an ethnolinguistics study, this research attempts to analyze the kinship terminology of two similar ethnic communities, Cina Benteng and Hakka (Khek) in Tangerang through the ethnolinguistic point of view. It aims to provide the kinship terminology in Cina Benteng and Khek and also to contrast the similarities and differences between the term of address and term of reference in the chosen communities. This research will utilize the kinship theory from Nanda, Burling, and Lounsbury. The data of this research are being collected by doing interviews, recording the interview, taking notes, dan observe the site. This research revealed that even though Cina Benteng and Khek communities belonged to the same root, they have some contrast in their referring and addressing system of kinship. AbstrakIstilah kekerabatan adalah kosakata yang digunakan untuk menyebut seseorang yang terikat dengan diri/penutur karena hubungan darah, keturunan, dan perkawinan. Istilah kekerabatan dalam sebuah bahasa terikat oleh budaya. Sistem kekerabatan dibahas secara luas dalam berbagai studi humaniora, termasuk linguistik. Istilah kekerabatan dalam sistem kekerabatan Cina Benteng dan Khek akan digunakan sebagai data atau bukti linguistik penelitian ini. Penelitian ini mencoba menganalisis terminologi kekerabatan dua komunitas etnis Tionghoa, yaitu Cina Benteng dan Hakka (Khek), di Tangerang dari sudut pandang etnolinguistik. Tujuan penelitian ini ialah mendeskripsikan istilah kekerabatan di Cina Benteng dan Khek serta untuk membandingkan persamaan dan perbedaan dari istilah kekerabatan dan sapaan di komunitas itu. Penelitian ini menggunakan teori kekerabatan dari Nanda, Burling, dan Lonsburry. Data penelitian ini dikumpulkan dengan melakukan wawancara, perekaman, pencatatan, dan pengamatan di lokasi. Hasil analisis menunjukkan bahwa meskipun berasal dari akar yang sama, komunitas Cina Benteng dan Khek memiliki beberapa perbedaan dalam sistem kekerabatan baik, dalam fungsi merujuk maupun memanggil.